General Anesthesia in a Patient With Neuronal Intranuclear Inclusion Disease: A Case Report. Issue 10 (18th October 2022) - Kinoshita, Michiko; Mutoh, Sarara; Kasai, Asuka; Kawanishi, Ryosuke; Tanaka, Katsuya
Abstract : Neuronal intranuclear inclusion disease (NIID) is a progressive neurodegenerative disease with diverse clinical manifestations, including dementia and muscle weakness. We summarize anesthetic considerations in reporting general anesthesia for a 58-year-old man with bladder dysfunction and cerebellar ataxia who was diagnosed with NIID. The patient developed postinduction hypotension relevant to autonomic neuropathy. The potential risks, such as prolonged reaction to neuromuscular blocking agent, postoperative delirium, and worsening of NIID-related symptoms, were also considered. The responsiveness to anesthetics may vary widely from case t case. As the number of NIID cases increases, a better understanding of NIID is needed.